1998
DOI: 10.1063/1.122927
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on Ga2O3(Gd2O3)/GaN metal–oxide–semiconductor field-effect transistors

Abstract: Ga 2 O 3 (Gd 2 O 3 ) was deposited on GaN for use as a gate dielectric in order to fabricate a depletion metal–oxide–semiconductor field-effect transistor (MOSFET). Analysis of the effect of temperature on the device shows that gate leakage is significantly reduced at elevated temperature relative to a conventional metal–semiconductor field-effect transistor fabricated on the same GaN layer. MOSFET device operation in fact improved upon heating to 400 °C. Modeling of the effect of temperature on contact resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
74
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 216 publications
(74 citation statements)
references
References 24 publications
0
74
0
Order By: Relevance
“…The insulated gate of the MOS structure reduces gate leakage current and therefore leads to increases in breakdown voltage. Gate dielectrics of AlN [1,2], Ga 2 O 3 (Gd 2 O 3 ) [1,3,4], SiO 2 [5,6], and Si 3 N 4 [7] have all been previously reported. From this research, interface state densities estimated as low as 5 Â 10 10 eV --1 cm --2 (SiO 2 /Si 3 N 4 /SiO 2 ) [8,9] and breakdown field strengths (E BD ) as high as 12.5 MV/cm (SiO 2 /Si 3 N 4 /SiO 2 ) have been measured.…”
mentioning
confidence: 99%
“…The insulated gate of the MOS structure reduces gate leakage current and therefore leads to increases in breakdown voltage. Gate dielectrics of AlN [1,2], Ga 2 O 3 (Gd 2 O 3 ) [1,3,4], SiO 2 [5,6], and Si 3 N 4 [7] have all been previously reported. From this research, interface state densities estimated as low as 5 Â 10 10 eV --1 cm --2 (SiO 2 /Si 3 N 4 /SiO 2 ) [8,9] and breakdown field strengths (E BD ) as high as 12.5 MV/cm (SiO 2 /Si 3 N 4 /SiO 2 ) have been measured.…”
mentioning
confidence: 99%
“…The degradation of the gate leads to premature breakdown and, hence, an adverse effect on device performances such as output power, rf efficiency, and noise figure. Such a premature breakdown is caused by the gate-drain diode breakdown as a result of the thermionic emission, crystal defects due to lattice mismatch, or the thermal effect as a consequence of the surface hopping conduction of the gate leakage current.Various gate insulation layers, such as SiO 2 , Si 3 N 4 , Ga 2 O 3 , and AlN have been employed as one of the possible solutions to solve the gate leakage problem by passivating the surface [6]. Other groups showed that a thin SiO 2 or Si 3 N 4 layer under the gate is effectively reducing the gate leakage current by several orders.…”
mentioning
confidence: 98%
“…1 Introduction A good materials combination for III-N compounds is of crucial importance in the field of Metal/Insulating/Semiconductor-based devices [1,2]. Currently, MIS-Field Effect Transistors (MIS-FET) include the use of AlN or Si 3 N 4 insulating layer [3,4].…”
mentioning
confidence: 99%